Evaluation of substrate composition for lignocellulolytic enzymes production by solid state fermentation of wastes from olive oil and wine industries - Salgado, José Manuel (2012)
Wastes from olive oil and wine industries (as exhausted grape mark, vineshoot trimmings, two-phase olive mill waste, vinasses and olive mill wastewater were evaluated for lignocellulolytic enzymes production (as cellulases, xylanases and feruloyl esterases) by solid state fermentation with Aspergillus niger, Aspergillus ibericus and Aspergillus japonicus. To study the effect of different substrates in enzymes production a Plackett-Burman experimental design was presented. The variables that had a higher positive effect in lignocellulolytic enzymes were urea, time and exhausted grape mark. The mixture of twophase olive mill waste with exhausted grape mark and vineshoot trimmings had maxima activity of cellulases, xylanases and feruloyl esterases.